Aneurysmal Bone Cysts of the Paranasal Sinuses: The Mayo Clinic Experience and Review of the Literature. (1st March 2021) - Smith, Alyssa J.; Choby, Garret; Van Gompel, Jamie J.; Link, Michael J.; Van Abel, Kathryn M.
Abstract : Objective/Hypothesis: Aneurysmal bone cysts (ABCs) are benign, lytic bone lesions, which rarely present in the paranasal sinuses. There is no published consensus on the appropriate diagnostic or treatment approach. Our objective was to elucidate the clinical behavior, treatment, and outcomes for patients with ABCs of the paranasal sinuses (psABCs). Study Design: Retrospective case series and system review of the literature. Methods: A retrospective chart review was performed to identify patients evaluated at the authors' institution with psABC and consolidated with literature reports of psABC. Results: Eighty‐nine patients met inclusion criteria. The most common presenting symptom was painless facial swelling (n = 35, 39%). The ethmoid sinuses were the most common site involved (n = 55, 62%). Surgical approach was reported in 74 cases including 20 endoscopic and 54 with an open or combined approach. Fifty‐nine patients (71%) underwent gross total resection. Follow up data was reported for 67 patients. Fifteen patients (22%) were found to have recurrence or progression at follow up; 10/15 (66%) patients within the first 12 months, 14/15 (93%) within the first 24 months, and 1/15 (7%) greater than 24 months after treatment. Patients were more likely to have recurrence/progression if they presented with nasal discharge ( P = .05), proptosis ( P = .01), or orbital involvement ( P = .03). Conclusions: psABCs typically present with painless swelling or nasal obstruction. Orbital involvement is a negative prognostic indicator with these patients more likely to have recurrence after treatment. Recurrence or progression of disease is most likely to occur within 2 years after treatment. Therefore, patients should be monitored closely during this time. Level of Evidence: 4 Laryngoscope, 131:E2525–E2533, 2021